Upaya Meningkatkan Kemampuan Memahami Struktur dan Kebahasaan Teks Iklan dengan Menerapkan Metode Inkuiri Siswa - I Wayan Agus Wiratama; Ni Putu Ayu Kartika Sari Dewi (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2023)
The low learning ability of students in understanding the structure and language of advertising is influenced by the not optimal implementation of learning structure and language of advertising texts. In addition, teachers are not optimal in utilizing learning methods in improving students' ability to understand the structure and language of advertising texts. The purpose of this study was to determine the increase in students' ability in understanding the structure and language of advertisement text. This research is a classroom action research consisting of two cycles with 30 students. The data collection method used is the observation method and the test method. The observation method is used to obtain data about students' attitudes and behavior. The test was used to determine students' ability to understand the structure and language of the advertisement text for class VIII C students of SMP Negeri 3 Tabanan for the 2021/2022 academic year after applying the inquiry method it has increased. This can be seen in the completeness of the students obtained in the pre-cycle, namely 36.66% with an average score of 62.33, the first cycle of students completed with a percentage of 26.66% with an average score of 68.66. The increase from cycle I to cycle II was 9.40%, in cycle II all students had passed (100%) with an average score of 80. Based on the results of data analysis, it can be concluded that by applying the inquiry method students' abilities have increased.